IMPLEMENTASI MULTICULTURAL BASED LEARNING DALAM MENINGKATKAN PRESTASI SISWA - Nafisa Feriana Feli; Syaiful lslam (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
In fact, multicultural education is an integral part of all levels of education. Therefore the cultivation of multicultural values is ideally applied in all subjects at all levels of formal education, but at the Insan Terpadu Middle School only specializes in citizenship education subjects. Multicultural is the process of developing attitudes and behaviors of a person or group of people in human maturation through teaching, coaching, training, processes, actions, and ways of educating or fostering human respect for plurality and diversity. Multicultural based learning in the Integrated Insan middle School using Curriculum 2013, by using curriculum 2013 educators will know the attitudes (characters) of students in each meeting. There are five dimensions of educators in implementing multicultural based education on student responses 1) (content integration), 2) (knowledge construction), 3) (prejudice reduction), 4) (equitable pedagogy), and 5) (empowering school culture social structure).